PERLINDUNGAN HUKUM KONSUMEN JASA PARKIR DITINJAU DARI HUKUM POSITIF - Edi Yanto; Imawanto Imawanto; Tin Yuliani (Universitas Muhammadiyah Mataram, 2020)
This article discusses the related problem of frequent loss of goods or vehicles in the parking area, causing disputes between consumers and parking managers. Most parking attendants do not want to be blamed for the loss of goods or consumer vehicles. Parking service managers always use the excuse that their work complies with the agreement or clause stated in the parking ticket, that is,